2009
DOI: 10.2169/internalmedicine.48.1999
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchitis in a Patient with Crohn's Disease

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Although bronchial dilation was attempted in that case, the procedure resulted in tracheal rupture and death (8). While gastrointestinal and respiratory symptoms were relieved simultaneously in most cases (9,13), the clinical courses of the upper airway and digestive diseases were not always entirely parallel (17). For example, in one case, the patient's respiratory status improved markedly with corticosteroid therapy, whereas the exacerbation of UC worsened, resulting in emergency colectomy for toxic megacolon (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although bronchial dilation was attempted in that case, the procedure resulted in tracheal rupture and death (8). While gastrointestinal and respiratory symptoms were relieved simultaneously in most cases (9,13), the clinical courses of the upper airway and digestive diseases were not always entirely parallel (17). For example, in one case, the patient's respiratory status improved markedly with corticosteroid therapy, whereas the exacerbation of UC worsened, resulting in emergency colectomy for toxic megacolon (7).…”
Section: Discussionmentioning
confidence: 99%
“…We describe the first case in Korea of tracheobronchial involvement in CD, which is rare even globally. Since Kraft et al [ 5 ] reported bronchopulmonary involvement in inflammatory bowel disease in 1976, only 13 cases including the present case (seven men and six women, ages 18 to 59 years; average age, 28 years) [ 3 ] have been reported, and the patient in our case is the youngest ( Table 1 ).…”
Section: Discussionmentioning
confidence: 67%
“…In the present case, as in previous cases, the pathologic findings of the bronchial biopsy were epithelial and subepithelial infiltrates of diverse types of inflammatory cells including neutrophils, macrophages, lymphocytes, and plasma cells [ 2 , 6 , 9 , 13 , 14 ]. According to Asami et al [ 3 ], bronchoscopic and pathologic findings such as these indicate that tracheobronchial inflammation results from the activation of macrophages and T lymphocytes, as does colonic inflammation. Previous reports also suggest that a common antigen triggers mucosal immune responses in both the GI tract and airway [ 2 , 6 , 9 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In refractory cases procedures like laser beam, balloon dilatation, stent placement or tracheotomy may be necessary to maintain patent airway. 10 , 11 , 12 , 13 , 20 , 21 , 22 , 23 , 24 According to our experience, in the first case the girl had evolution to respiratory failure in spite of inhaled corticosteroid therapy. This highlights the fact that inhaled administration may not be efficient enough in severe cases.…”
Section: Discussionmentioning
confidence: 79%